Proliferative glomerulonephritis with monoclonal immunoglobulin deposits (PGNMID): three Case Reports and systematic review - Ji, Quanying; Yu, Shuyuan; Zhou, Xia; Wang, Zhenhua; Guo, Xiaoqing; Zhong, Yuping (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to investigate the clinical characteristics and personalized treatment strategies for proliferative glomerulonephritis with monoclonal immunoglobulin deposits (PGNMID).MethodsA retrospective analysis was conducted on the clinical features, pathological characteristics, and treatment regimens of three PGNMID patients.ConclusionProliferative glomerulonephritis with monoclonal immunoglobulin deposits patients commonly present with proteinuria, hematuria, and renal insufficiency. Pathologically, light microscopy predominantly reveals a membranoproliferative glomerulonephritis (MPGN) pattern, with IgG3κ being the most prevalent immunohistochemical subtype. Current guidelines recommend the BCD regimen (bortezomib, cyclophosphamide, dexamethasone) as first-line therapy. Daratumumab may be a safe and effective therapeutic option for PGNMID; however, clinical decision-making should comprehensively consider patient age, renal function status, treatment tolerance, and other factors.